Α‐enolase promotes tumorigenesis and metastasis via regulating AMPK/mTOR pathway in colorectal cancer. Issue 5 (12th January 2017) - Zhan, Panpan; Zhao, Shihu; Yan, Hua; Yin, Chunli; Xiao, Yi; Wang, Yunshan; Ni, Ruoxuan; Chen, Weiwen; Wei, Guangwei; Zhang, Pengju
Abstract : The α‐enolase (ENO1) plays pivotal roles in several types of cancer, but its clinical significance, functional role, and possible mechanism in colorectal cancer (CRC) have remained unclear. Expression level of ENO1 in CRC tissues was examined by qRT‐PCR, Western blot, and immunohistochemistry. The effects of ENO1 on cell growth were investigated by MTT, colony formation, flow cytometry assays, and in vivo tumorigenic capacity analysis. The impacts of ENO1 on cell migration and invasion were also explored by scratch‐healing, Transwell or Matrigel chamber assays, and in vivo metastatic capacity analysis. Our results showed that the expression level of ENO1 was significantly elevated in CRC tissues. High expression level of ENO1 was associated with disease progression in CRC patients. Overexpression of ENO1 in HCT116 cell line promoted cell proliferation, migration, and invasion in vitro as well as tumorigenesis and metastasis in vivo . In other hand, ablation of ENO1 in HCT116 cells led to totally reverse effects. Mechanistically, we revealed ENO1 could regulate AMPK/mTOR signaling pathway. AMPK pathway activation or mTOR pathway suppression blocked these ENO1 induced alterations. Together, our results demonstrated that ENO1 is a potent promoter of CRC genesis and metastasis at least in part though regulating AMPK/mTOR pathway. These findings also suggested that ENO1 may be a promising therapeutic target in CRC patients.